'Barbarity more suited to Savages': British soldiers' views of Spanish and Portuguese violence during the Peninsular War, 1808–1814. (1st October 2016) - Daly, Gavin
Abstract : This article explores British soldiers' reactions to the violence that Iberian soldiers, guerrillas and civilians perpetrated against wounded French soldiers and prisoners of war during the Peninsular War. Whilst they saw this violence as retaliatory, and sympathized with the suffering of the occupied, British soldiers were shocked, disturbed and outraged, often leading them to self-identify with their very enemy — the French. On one level, this violence was seen as a fundamental violation of customary rules of war. Yet further, in British minds it revealed a deeper Iberian culture of violence and way of war, which set the Iberian peoples apart from 'civilized' nations.